Understanding Non-Completion of the Human Papillomavirus Vaccine Series: Parent-Reported Reasons for Why Adolescents Might Not Receive Additional Doses, United States, 2012 - Clark, Sarah J. (Public Health Rep, 2016)
Completion rates of the human papillomavirus (HPV) vaccine series among U.S. adolescents are below public health targets. We explored parent-reported reasons for their children's non-completion of the HPV vaccine series using a nationally representative online survey of parents of children aged 9–17 years, fielded in October 2012. Among the 1,653 parents who responded, the proportion reporting that their child would definitely continue with the HPV vaccine series among those who had started the series ranged from 28% to 54%. The most common reason cited by parents for non-completion of the series was their child's fear of needles, followed by lack of awareness about additional doses and safety concerns. These findings demonstrate the need to encourage adoption of strategies addressing needle fears, utilize reminders for parents about subsequent doses, and emphasize recent HPV vaccine safety data in discussions with parents.